Non-canonical Wnt signalling regulates scarring in biliary disease via the planar cell polarity receptors - D. H. Wilson (Nature Portfolio, 2020)
In fibrotic biliary disease, portal fibroblasts promote both biliary scarring and bile duct regeneration. Here, the authors report that the non-canonical Wnt-PCP signalling promotes bile duct scarring in mice, and inhibition of Wnt-ligands reduces the scarring without impairing regeneration.